The peri-urban interface and house infestation with Triatoma infestans in the Argentine Chaco: an underreported process? - Provecho, Yael Mariana (2014)
Peri-urban infestations with triatomine bugs, their sources and their dynamics have rarely been investigated. Here, we corroborated the reported occurrence of Triatoma infestans in a peri-urban area and in neighbouring rural houses in Pampa del Indio, in the Argentine Chaco, and identified its putative sources using spatial analysis and demographic questionnaires. Peri-urban householders reported that 10% of their premises had triatomines, whereas T. infestans was collected by timed manual searches or community-based surveillance in only nine (3%) houses. Trypanosoma cruzi-infected T. infestans and Triatoma sordida were collected indoors only in peri-urban houses and were infected with TcV and TcI, respectively. The triatomines fed on chickens, cats and humans. Peri-urban infestations were most frequent in a squatter settlement and particularly within the recently built mud houses of rural immigrants, with large-sized households, more dogs and cats and more crowding. Several of the observed infestations were most likely associated with passive bug transport from other sources and with active bug dispersal from neighbouring foci. Thus, the households in the squatter settlement were at a greater risk of bug invasion and colonisation. In sum, the incipient process of domestic colonisation and transmission, along with persistent rural-to-urban migratory flows and unplanned urbanisation, indicate the need for active vector surveillance and control actions at the peri-urban interface of the Gran Chaco.